DEEPFAKE TECHNOLOGY THROUGH KANTIAN DEONTOLOGY LENS: A HYBRID SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Achmad Syahrully Bachri; Azwar Azwar; Ana Kuswanti; Kusumajanti Kusumajanti (Lektur: Jurnal Ilmu Komunikasi, 2026)
This study systematically maps the global research landscape on deepfake technology and evaluates its ethical implications through the lens of Kantian Deontology to bridge the gap between technical and ethical perspectives. Using a Systematic Literature Review approach, the study focuses on the term “Deepfake Technology” in article titles, abstracts, and keywords in the Scopus database, resulting in 148 articles published between 2019 and 2025, with data assessed on November 7, 2025. The retrieved documents are analyzed bibliometrically using VOSviewer to identify publication trends, authorship patterns, and thematic clusters. The findings show that current scholarship is predominantly technical, with a strong emphasis on detection algorithms and major contributions from China and India. Ethically, the analysis concludes that non-consensual and deceptive deepfakes are morally impermissible because they violate the Kantian principles of universalizability and respect for human dignity. The study also uncovers substantial gaps in communication and ethical research, from which five practical ethical guidelines and a conceptual governance model are proposed to support more responsible development and regulation of deepfake technology.